2011
DOI: 10.1093/sleep/34.5.575
|View full text |Cite
|
Sign up to set email alerts
|

Short or Long Sleep Duration Is Associated with Memory Impairment in Older Chinese: the Guangzhou Biobank Cohort Study

Abstract: Short or long sleep duration was an important sleep-related factor independently associated with memory impairment and may be a useful marker for increased risk of cognitive impairment in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 29 publications
7
120
3
4
Order By: Relevance
“…20,21 Sleep deprivation degrades the peak circadian drive for wakefulness over time and affects neural processing, resulting in the destabilization of the wake state and overall neurocognitive function. The negative impact of these neurocognitive effects are particularly evident in the prefrontal cortex, the area of the brain related to attention and working memory abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Sleep deprivation degrades the peak circadian drive for wakefulness over time and affects neural processing, resulting in the destabilization of the wake state and overall neurocognitive function. The negative impact of these neurocognitive effects are particularly evident in the prefrontal cortex, the area of the brain related to attention and working memory abilities.…”
Section: Discussionmentioning
confidence: 99%
“…22 Previous studies have also found that long sleep duration may contribute to variation in cognitive test performance, as was observed in the present study. 4,21 Long sleep duration may simply reflect the presence of sleep disorders or other illnesses. These individuals may require more time in bed to feel rested and therefore report longer sleep durations.…”
Section: Discussionmentioning
confidence: 99%
“…Some reported poor cognition in older persons sleeping for longer duration (Faubel et al 2009;Benito-Leon et al 2009;Schmutte et al 2007) while others demonstrated the opposite (Ohayon and Vecchierini 2005;Tworoger et al 2006). Kronholm et al (2009), furthermore, has revealed an inverted U-shaped relationship between sleep duration and cognitive function in the general population, while Xu et al (2011) have recently reported a similar relationship in older adults. While the duration or quantity of sleep is significant, the quality of sleep may be related to cognitive decline too.…”
Section: Introductionmentioning
confidence: 99%
“…1 Chronic insomnia, prolonged daytime sleepiness, and long sleeping have been associated with poorer cognitive function. [2][3][4][5][6] However, the contribution of sleep problems to the risk of dementia is poorly understood. Only 2 groups have examined this association.…”
mentioning
confidence: 99%